2022
DOI: 10.1101/2022.06.28.498024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The LncRNA Carmn is a Critical Regulator for Gastrointestinal Smooth Muscle Contractile Function and Motility

Abstract: Background & aimsVisceral smooth muscle cells (SMCs) are an integral component of the gastrointestinal (GI) tract and are critical for regulating motility. SMC contraction is regulated by changes in post-translational signaling and the state of differentiation. Impaired SMC contraction is associated with significant morbidity and mortality but the mechanisms regulating the expression levels of SMC-specific contractile proteins, including the role of long non-coding RNAs (lncRNAs), remains largely unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Interestingly, unlike other SMC-enriched genes that are expressed in both vascular and visceral SMCs of GI tissues such as MYOCD 32 , LMOD1 33 and CARMN 34 , PRDM16 exhibits negligible expression in GI tissues and visceral SMCs (Figure 1D-G & Online Figure S3-5). Previous studies showed that global or SMC-specific knockout of these pan SMC-enriched genes in mice often leads to lethal GI phenotypes [35][36][37] , which largely impedes the efforts for investigating their vascular function. Therefore, the VSMC-enriched expression pattern of PRDM16 offers a unique opportunity to study its function in VSMCs and vascular disorders by inherently circumventing GI phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, unlike other SMC-enriched genes that are expressed in both vascular and visceral SMCs of GI tissues such as MYOCD 32 , LMOD1 33 and CARMN 34 , PRDM16 exhibits negligible expression in GI tissues and visceral SMCs (Figure 1D-G & Online Figure S3-5). Previous studies showed that global or SMC-specific knockout of these pan SMC-enriched genes in mice often leads to lethal GI phenotypes [35][36][37] , which largely impedes the efforts for investigating their vascular function. Therefore, the VSMC-enriched expression pattern of PRDM16 offers a unique opportunity to study its function in VSMCs and vascular disorders by inherently circumventing GI phenotypes.…”
Section: Discussionmentioning
confidence: 99%